Fundamentals of Human Resource Management / Raymond A. Noe [et..al], - Noe, Raymond A. (McGraw-Hill Education, 2018)
Provides a complete introduction to human resource management for the general business manager who wants to learn more about how HRM is used in the everyday work environment.